Sistem Informasi Pembelian dan Penjualan pada Divisi HANDAKKOM PT. PINDAD (PERSERO) Bandung - Sintya Sukarta; Finna Silfiana (Universitas Sahid Surakarta, 2012)
HANDAKKOM is one of the divisions contained in the company of PT.PINDAD (Persero) Bandung. This Division has activities in the sale and purchase of explosives intended for commercial use. In data processing, this division is still done manually. This can slow down the processing of data so. The purpose of this research was to design a Purchase and Sale information system to store data properly, can automatically update stock material, and may make purchases and sales reports quickly. The research method used in this design is a method that is a structured approach with tools flowmap, data flow diagram (DFD) and Entity Relationship Diagram (ERD). As for the method used for the development systems was the prototype method.